Peranan Media Massa Dalam Pembentukan Kepribadian Pelajar Muslim (Kajian Perbandingan di Kajang dan Sabak Bernam) - Kamarudin Salleh (Millah: Journal of Religious Studies, 2005)
This article intends to delineate the role and impact of mass media, whether electronic or printed toward the forming and developing the Muslim adolescent personality. This study is run in comparison between two areas; town (Kajang) and rural (Sahak Bernam) in Selangor, Malaysia. The findings of research show that, some students confess that they are attract and eager to the advertisements and programmes airing on TV, radio, magazine, newspaper and so on. Then, to certain extent, trying to imitate or follow that artists. Finally, some suggestions are putting in order to control and avoid the spread of social ills among adolescent.